Moldova Policy Notes 2019 : Enhancing Water Security and Service Delivery - Smets, Susanna (Washington, DC: World Bank, 2020)
Water security is vital to Moldova’s economic development, environmental sustainability, and social inclusion. Moldova’s water-related opportunities and risks are shaped by factors both within and outside the water sector. Rural areas are poorly served by drinking water and sanitation services because of low investment, inadequate service delivery, and lack of assistance to rural municipalities. Moldova needs to embark on a more holistic and multisectoral programmatic approach for managing the country’s water resources, risks, and services, both rural and urban. This policy note emphasizes on the actions going forward needed to manage the water resources effectively.